2022
DOI: 10.1371/journal.ppat.1010915
|View full text |Cite
|
Sign up to set email alerts
|

Unique cellular immune signatures of multisystem inflammatory syndrome in children

Abstract: The clinical presentation of MIS-C overlaps with other infectious/non-infectious diseases such as acute COVID-19, Kawasaki disease, acute dengue, enteric fever, and systemic lupus erythematosus. We examined the ex-vivo cellular parameters with the aim of distinguishing MIS-C from other syndromes with overlapping clinical presentations. MIS-C children differed from children with non-MIS-C conditions by having increased numbers of naïve CD8+ T cells, naïve, immature and atypical memory B cells and diminished num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…In addition, IL‐6, IL‐1β, and IL‐12 have been consistently implicated in severe disease 13 . We have previously demonstrated that children with COVID‐19 also show a distinct cytokine/chemokine upregulation as well as alterations in acute phase proteins, complement components and MMPs 14–18 . However, in this study, we show that although most of the pro‐inflammatory cytokines, chemokines, growth factors, and acute phase proteins were elevated in children, they were significantly decreased in children compared to the elderly population.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In addition, IL‐6, IL‐1β, and IL‐12 have been consistently implicated in severe disease 13 . We have previously demonstrated that children with COVID‐19 also show a distinct cytokine/chemokine upregulation as well as alterations in acute phase proteins, complement components and MMPs 14–18 . However, in this study, we show that although most of the pro‐inflammatory cytokines, chemokines, growth factors, and acute phase proteins were elevated in children, they were significantly decreased in children compared to the elderly population.…”
Section: Discussioncontrasting
confidence: 58%
“…13 We have previously demonstrated that children with COVID-19 also show a distinct cytokine/ chemokine upregulation as well as alterations in acute phase proteins, complement components and MMPs. [14][15][16][17][18] However, in this study, we show that although most of the pro-inflammatory cytokines, chemokines, growth factors, and acute phase proteins were elevated in children, they were significantly decreased in children compared to the elderly population. Our results are similar to the finding by Pierce et al, 13 where they showed decreased levels of IL-6, TNFα, and IP-10 compared to adults.…”
Section: Discussionmentioning
confidence: 76%
“…1). Given that immunothrombosis is common in COVID-19 and the complement system likely contributes to these responses (22)(23)(24), we heated and inactivated plasma from PASC donors at 55˚C and repeated the experiments. We observed that platelets were persistently activated if spiked with room temperature plasma or heat-inactivated plasma prior to agonist stimulation from PASC patients suggesting that complement activation is unlikely to be a driver in the augmented platelet response observed (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that children with MIS have presented with lymphopenia, which would thereby lead to a weakened immune system in the host ( 2 ). A cellular study on MIS-C immune signatures showcases reduced CD4 + and CD8 + T-cell memory subsets in children with MIS ( 14 ). Similarly, the downregulation of host-protecting T-cell responses was suggested as evidence of MIS-C and COVID-19 infection ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of components of the innate immune response in MIS-C showed marked neutrophil activation, degranulation signatures, and neutrophil extracellular traps ( 13 ). Rajamanickam et al explored cellular biomarkers for MIS-C, inclusive of B cells, dendritic cells, monocytes, and T cells, which significantly distinguish MIS-C from other diseases that have overlapping clinical symptoms ( 14 ). Moreover, HLA-genotype alterations in the T cells of children with MIS were reported as MIS-C biomarkers ( 15 ).…”
Section: Introductionmentioning
confidence: 99%